The body as site of interweaving performance cultures: Between being a body and having a body. Issue 2 (1st October 2017) - Fischer-Lichte, Erika
This article deals with problems arising from the globalization of 'embodied knowledge' in the performing arts. Proceeding from the theories of Marcel Mauss and Hellmuth Plessner, the article introduces the concepts of the body-object and the body-subject, and discusses whether embodied knowledge only refers to certain specific body techniques, which will only impact upon the body as the object, or whether it also impacts upon the body as the site of the subject. Whether or not embodied knowledge practised by an actor/performer is part of a much broader field of knowledge, such as aesthetics, philosophy or religion, is also an important question that contributes to the fundamental argument of the article. To shed light on this issue, the article examines two treatises on acting from two different cultures, Bharata Muni's the Natyasastra (second century bce and second century ce) and Johann Jakob Engel's Practical Illustrations of Rhetorical Gestures and Action (1785–86), in order to evaluate their proposal on how to represent emotions in performance and what kinds of responses this may elicit from spectators. Similarly, I will examine two modes of interweaving performance practice: first, the actors who were trained in one particular style or tradition but acquired the bodily techniques of another cultural style later in their performance career; and second, the co-performing actors who were trained in and belonged to different performance traditions yet worked together onstage.